1999
DOI: 10.1007/s002040050636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute and chronic hepatotoxic effects exerted by anabolic-androgenic steroid stanozolol in adult male rats

Abstract: Stanozolol (ST) is a 17alpha-alkyl anabolic-androgenic steroid (17alpha-AAS) often misused by athletes and bodybuilders. The use of anabolic-steroids by sportsmen and teenagers has increased dramatically, thus raising the question about their hepatotoxicity, specially those such as ST which are orally administered. Previously, we have reported diverse in vivo effects exerted by this steroid and published the existence of a highly specific ST-binding site in male rat liver microsomes. The existence of this bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 19 publications
4
45
0
2
Order By: Relevance
“…Accordingly, chronic use of AAS leads to structural and functional changes in the liver such as cholestatic jaundice, peliotic hepatic hyperplasia and hepatocellular adenomas (Fortunato et al, 2006). Moreover, Boada et al (1999) observed that rats treated with high doses of Stanozolol showed inflammation or degeneration of the central lobe of the liver, a change which is proliferant in all hepatocytes. Burghardt et al (2004) studied the effects of chronic treadmill training on behavioral parameters in rats and concluded that the exploratory locomotor activity, assessed using the open field method, was reduced after training.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, chronic use of AAS leads to structural and functional changes in the liver such as cholestatic jaundice, peliotic hepatic hyperplasia and hepatocellular adenomas (Fortunato et al, 2006). Moreover, Boada et al (1999) observed that rats treated with high doses of Stanozolol showed inflammation or degeneration of the central lobe of the liver, a change which is proliferant in all hepatocytes. Burghardt et al (2004) studied the effects of chronic treadmill training on behavioral parameters in rats and concluded that the exploratory locomotor activity, assessed using the open field method, was reduced after training.…”
Section: Discussionmentioning
confidence: 99%
“…However, biochemical examination has yet to reveal liver dysfunction under these circumstances. Boada et al reported that high doses of stanozolol treatment in male rats resulted in inflammation or degeneration in central lobular hepatocytes and exert a proliferative effect on liver cells [43]. Furthermore, there are some reports indicating that levels of cytocrome P-450 in the liver are decreased in male rats following AAS administration [44].…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry analysis by fine-needle aspiration was carried out immediately. Fine-needle aspiration (25-gauge) was used to obtain liver nuclei from liver specimens, which were processed as described previously (Vindelov and Christensen 1990;Doolittle et al 1992;Boada et al 1999;Torres et al 1999). Cell nuclei were analysed on an EPICS XL-MCL cytometer (Coulter Corporation, Hialeah, Fla., USA).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…The liver effects were analysed in a time-course model (1 day, 5 days and 10 days) in order to evaluate the possible accumulative toxicity. The route of administration was chosen to ensure that as high a quantity of PR as possible was absorbed and distributed throughout the animal tissues and to enhance the sensitivity of the assay (Ha¨llstro¨m et al 1996;Boada et al 1999). The dose of this progestagen selected was the minimal one capable of inducing a clear reproductive effect in our animal model (significant decrease in testis weight and/or cryptorchidism).…”
Section: Introductionmentioning
confidence: 99%